Calcium Oxalate Crystals (CaOx) on Porang (Amorphopallus muelleri Blume) Exposed and Unexposed Sun - Nurul Chairiyah; Nunung Harijati; Retno Mastuti (Natural B, Journal of Health and Environmental Sciences, 2011)
Sunlight was suspected to affect CaOx crystal formation in porang. This research had aim to determine variations in forms of CaOx crystals and the influence of shade on the density of CaOx crystals in porang. Preparations for microscopic observation derived from sliced leaf, petiole, and tuber of porang that grown under shaded and exposed to sunlight conditions. Sliced organ was cleared by using the modified clearing method. The parameters that observed included shape, shape variety, and density of CaOx crystals. CaOx crystal density were analyzed using ANOVA followed by Tukey (α 0.05). The differences of crystal density between the edges and middle of the organ were analyzed using Paired Samples T Test. Microscopic observation showed that CaOx crystals were grouped into large (20-710 m) and small (1-15 m) crystals size. The density of CaOx crystals in plants exposed to sunlight was 3 times higher than the shaded plants. Leaf organ had the highest number of crystal compared to others organ. The tuber had the lowest density of CaOx crystals among organ. In addition, the shaded or exposed to sunlight condition had no effect on CaOx crystal density between the edges and center of the organ.